Peroxynitrite Exposure of CXCL12 Impairs Monocyte, Lymphocyte and Endothelial Cell Chemotaxis, Lymphocyte Extravasation in vivo and Anti-HIV-1 Activity - Janssens, Rik; Boff, Daiane; Ruytinx, Pieter; Mortier, Anneleen; Vanheule, Vincent; Larsen, Olav; Daugvilaite, Viktorija; Rosenkilde, Mette M.; Noppen, Sam; Liekens, Sandra; Schols, Dominique; De Meester, Ingrid; et al. (Frontiers in Immunology, 2018)
CXCL12 is a chemotactic cytokine that attracts many different cell types for homeostasis and during inflammation. Under stress conditions, macrophages and granulocytes produce factors such as peroxynitrite as a consequence of their oxidative response. After short incubations of CXCL12 with peroxynitrite, the gradual nitration of Tyr7, Tyr61 or both Tyr7 and Tyr61 was demonstrated with the use of mass spectrometry, whereas longer incubations caused CXCL12 degradation. Native CXCL12 and the nitrated forms, [3-NT61]CXCL12 and [3-NT7/61]CXCL12, were chemically synthesized to evaluate the effects of Tyr nitration on the biological activity of CXCL12. All CXCL12 forms had a similar binding affinity for heparin, the G protein-coupled chemokine receptor CXCR4 and the atypical chemokine receptor ACKR3. However, nitration significantly enhanced the affinity of CXCL12 for chondroitin sulfate. Internalization of CXCR4 and beta-arrestin 2 recruitment to CXCR4 was significantly reduced for [3-NT7/61]CXCL12 compared to CXCL12, whereas beta-arrestin 2 recruitment to ACKR3 was similar for all CXCL12 variants. [3-NT7/61]CXCL12 was weaker in calcium signaling assays and in in vitro chemotaxis assays with monocytes, lymphocytes and endothelial cells. Surprisingly, nitration of Tyr61, but not Tyr7, partially protected CXCL12 against cleavage by the specific serine protease CD26. In vivo, the effects were more pronounced compared to native CXCL12. Nitration of any Tyr residue drastically lowered lymphocyte extravasation to joints compared to native CXCL12. Finally, the anti-HIV-1 activity of [3-NT7]CXCL12 and [3-NT7/61]CXCL12 was reduced, whereas CXCL12 and [3-NT61]CXCL12 were equally potent. In conclusion, nitration of CXCL12 occurs readily upon contact with peroxynitrite and specifically nitration of Tyr7 fully reduces its in vitro and in vivo biological activities.